Middle airway obstruction—it may be happening under our noses. Issue 4 (19th July 2012) - Bardin, Philip G; Johnston, Sebastian L; Hamilton, Garun
Abstract : Background: Lower airway obstruction has evolved to denote pathologies associated with diseases of the lung, whereas, conditions proximal to the lung embody upper airway obstruction. This approach has disconnected diseases of the larynx and trachea from the lung, and removed the 'middle airway' from the interest and involvement of respiratory physicians and scientists. However, recent studies have indicated that dysfunction of this anatomical region may be a key component of overall airway obstruction, either independently or in combination with lung disease. New diagnostic modalities to effectively diagnose middle airway obstruction are being developed, and it has become feasible to identify and quantify middle airway obstruction. Conclusion: We, therefore, propose adding 'middle airway obstruction' to our nomenclature to embed it in diagnostic approaches, and to allow due emphasis on this neglected anatomical region.